Deeply responsible business a global history of values-driven leadership - Jones, Geoffrey (Harvard University Press, 2023)
Deeply Responsible Business profiles corporate leaders of the past two centuries who made social missions vital to their businesses. Geoffrey Jones explores the characters and motivations of fourteen such leaders and compares their deep social and environmental commitments to the lukewarm "corporate social responsibility" of today.